Desperation, miserability and repugnance: harmful effects in some erotic-loving experiences described by Catulus - de Assis, Jean Felipe (Romanitas - Revista de Estudos Grecolatinos, 2022)
After translating Catullus’ poem LXXXVI, some damagingeffects from erotic-loving experiences are visible throughout the lover’s experience of despair and miserability. Such conditions are resultant of the maintenance of fides and pietas, famous conceptions in the Latin epics that are re-signified in urban environments at the end of the republican period. In this context, a destruction of persona animus and a repugnance feeling pervade the lover as a whole, making him unable to live with dignity neither to civil conceptions, nor to individual predispositions. The Servitum Amoris, member of Venus’ hosts, Militia Amoris, calls for divine intervention and seeks to return to the negotium in order to achieve his well-being. A comparative analysis with other poems in Catullus’ collection corroborates, not only aesthetic receptions from multiple hellenistic traditions in Latin literature, but also unveils social transformations in Roman Urbs, mainly due to re-significations of traditional conceptions.
Keywords: Catullus; Elegies; Fides; Pietas; Servitum Amoris; Militia Amoris